Immunoelectron microscopic localization of outer membrane proteins II on the surface of Neisseria gonorrhoeae. - Robinson, E N (1988)
To determine the ultrastructural distribution and immunological accessibility of proteins II (P.IIs) on the surfaces of whole gonococci, anti-P.II gold probes were developed and used in electron microscopic studies of viable P.II-expressing variants of Neisseria gonorrhoeae FA1090. Anti-P.II probes clearly marked the surfaces of organisms and their associated outer membrane blebs. The surface-exposed portion of P.II is antigenically variable. With the use of two different sizes of gold probes, it was demonstrated that individual gonococcal cells can express more than one antigenic type of P.II simultaneously.